Synthesis of several types of 2, 8-dioxabicyclo[3.3.1]nonanes using amberlyst-15 as an efficient recyclable heterogeneous catalyst. Issue 23 (2nd December 2017) - Samanta, Swati; Sepay, Nayim; Mallik, Sumitava; Mondal, Rina; Rahaman Molla, Mosidur; Mallik, Asok K.
ABSTRACT: A facile synthesis of 2, 8-dioxabicyclo[3.3.1]nonane derivatives starting from simple molecules, such as 2-hydroxychalcones as one component and dimedone, 4-hydroxycoumarin, 2-hydroxynaphthoquinone, 2-naphthol or 1-naphthol, as the other has been achieved by use of amberlyst-15, a sulfonated polystyrene resin, as a recyclable heterogeneous catalyst. The methodology involves a domino sequence of Michael addition and two-stage cyclisation. GRAPHICAL ABSTRACT: